2022
DOI: 10.3390/ijerph19116837
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders Associated with Occupational Driving: A Systematic Review Spanning 2006–2021

Abstract: Several occupations require workers to spend long periods of time driving road vehicles. This occupational task is associated with musculoskeletal disorders. The purpose of this review was to collate, synthesize, and analyze research reporting on musculoskeletal disorders associated with occupational driving, in order to develop a volume of evidence to inform occupational disorder mitigation strategies. A systematic search of academic databases (PubMed, EBSCO host, CINAHL, SPORTDiscus, and Web of Science) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 88 publications
0
11
0
1
Order By: Relevance
“…On the other hand, the current study found a higher prevalence of LBP than those studies in different regions, including Turkey (49.7%),15 Malaysia (48.5),34 Ghana(34.3%),9 Saudi Arabia (60.7%),11 China, (54%)13 and Addis Ababa, Ethiopia (64.2%) 16. The possible reason for this difference could be due to differences in the awareness level of LBP and differences in the measurement of LBP, vehicle ergonomics7 and driving hours per day; for example, in Gondar, 28% and in Malaysia, 43.5% drivers work less than 10 and 8 hours/day, respectively 34. The other reason for this difference might be, during the data collection period around 12.6 km roads among the main routes of the city were under upgrading construction due to which roads were very rough and gravel and earth-made roads which are low-quality roads would expose drivers to whole body vibration35 and these exposures might contribute for higher LBP development 36 37…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the current study found a higher prevalence of LBP than those studies in different regions, including Turkey (49.7%),15 Malaysia (48.5),34 Ghana(34.3%),9 Saudi Arabia (60.7%),11 China, (54%)13 and Addis Ababa, Ethiopia (64.2%) 16. The possible reason for this difference could be due to differences in the awareness level of LBP and differences in the measurement of LBP, vehicle ergonomics7 and driving hours per day; for example, in Gondar, 28% and in Malaysia, 43.5% drivers work less than 10 and 8 hours/day, respectively 34. The other reason for this difference might be, during the data collection period around 12.6 km roads among the main routes of the city were under upgrading construction due to which roads were very rough and gravel and earth-made roads which are low-quality roads would expose drivers to whole body vibration35 and these exposures might contribute for higher LBP development 36 37…”
Section: Discussionmentioning
confidence: 99%
“…Lower back pain is very common among truck, bus and taxi drivers and is one of the most commonly reported occupational health problems among professional drivers 7. The magnitude of LBP among taxi drivers has been reported in different studies, such as Iran, 51.2%,8 Ghana, 34.3%,9 Taiwan, 51%,10 Saudi Arabia, 60.7%,11 Cameron, 72.8%,12 China, 54%,13 Hungary, 61.36%,14 Turkey, 49.7%,15 Addis Ababa, Ethiopia, 64.2%,16 Tigray, Ethiopia, 27.9% 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En esa línea, se ha visto una alta prevalencia en conductores profesionales, siendo la zona lumbar reportada en el estudio de Joseph et al (28) la más afectada, cuyos factores de riesgos pueden ser mitigados a través de programas de estiramiento, junto con la educación vial. (29) Las limitaciones del presente estudio se circunscriben a las bases de datos consultadas y, por consiguiente, a la muestra identificada. En lo referente a las fortalezas, la presente revisión corresponde a la primera que se tiene conocimiento que brinde variadas intervenciones incluyendo distintos niveles de la gestión en salud, desde aspectos asistenciales, ambientales e inclusive de abordaje estratégico.…”
Section: Discussionunclassified
“…Greater adherence to the ergonomics process would seem the most preferred strategy for getting long term prevention of these problems within the UK and elsewhere [14]. According to study report in truck, bus, and taxi drivers the most common risk factors for these occupations include long hours in a sitting position, years in the profession, vehicle ergonomics, and vibration [15]. The implanting health education and awareness programs about LBP and its risk factors is discussed in this study and prevalence was high among car drivers [16].…”
Section: Discussionmentioning
confidence: 99%